Online interprofessional simulation for undergraduate health professional students during the COVID-19 pandemic. Issue 5 (2nd September 2020) - Prasad, Namrata; Fernando, Shavi; Willey, Sue; Davey, Kym; Kent, Fiona; Malhotra, Atul; Kumar, Arunaz
ABSTRACT: This report describes the Obstetric and Neonatal Simulation (ONE-Sim) workshop run in a remote learning format for medical and midwifery students in an interprofessional setting during the COVID-19 pandemic. It explores the observation of students as participants in the online learning of using Personal Protective Equipment and simulation-based learning of perinatal emergency management. This was followed by their mutual interaction and reflections. This paper aims to understand the role of synchronous remote learning through simulation and its impact on interprofessional interactions. We describe the experience of medical and midwifery students with the ONE-Sim workshop, facilitated by medical (obstetric and neonatal) and midwifery educators. Formal thematic analysis will be performed as part of the ongoing study; however, initial direct observation demonstrated that students reacted positively to the online ONE-Sim workshop and engaged well with facilitators and peers. Students mutually interacted amongst themselves, shared their previous experiences, knowledge of roles as medical and midwifery practitioners and how they see themselves in those roles in a perinatal emergency setting. The initial observations demonstrate that interprofessional education delivered in an e-learning format can be useful and meaningful, and may be utilized across a number of specialties.